PROSEDUR PEMBERIAN KREDIT PADA LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT CENGKILUNG DENPASAR UTARA - Ni Luh Dia Ayu Ningtias; Ni Putu Trisna Windika Pratiwi; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2020)
LPD is a financial institution belonging to the Pakraman village that participates in the success of development, especially in the field of the village economy. The research with the title "Procedure for Providing Credit to Village Credit Institutions (LPD) in Cengkilung Traditional Village, North Denpasar", has a formulation of the problem. The purpose of this study was to determine the procedures applied by the LPD Desa Adat Cengkilung Denpasar in considering granting credit to prospective debtors. This research uses observational research methods, interviews, and documentation. The data sources used are secondary data, as well as data such as the history of the establishment of the LPD, organizational structure, creditors recapitulation, income statements, and balance sheets. This research uses comparative descriptive analysis technique. Based on the research conducted, it was found that the Cengkilung LPD in providing credit had not followed all the credit granting procedures in force in the Cengkilung Traditional Village LPD. The implementation of the credit distribution policy at the Cengkilung Traditional Village LPD has not yet referred to the prudential principle in lending.